Effects of supplementation of different levels of organic acids mixture to the diet on performance, egg quality parameters, serum traits and histological criteria of laying hens - Kaya, Hatice; Kaya, Adem; Gul, Mehmet; Celebi, Saban; Timurkaan, Sema; Apaydin, Betul (Eugen Ulmer Gmbh Co, 2014)
This study was conducted to determine the effects of an organic acid mixture (OAM) (70% propionic acid, 5% citric acid, 25% soft acid) supplementation at various levels on performance, egg quality parameters, serum traits, and histological criteria in laying hens. Lohman layers (N = 72) were divided into four groups. The treatment groups were placed in six cages containing three hens each. The hens were fed either a control diet or the control diet supplemented with OAM (0, 1.5, 3.0 or 4.5 kg/t of feed) from 26 to 38 weeks of age. With the exception of egg production, final body weight and body weight change, there was a cubic effect on feed consumption, egg weight and feed conversion ratio with increasing levels of OAM supplementation. Shell strength (cubic) and yolk color (linear) increased as the level of OAM supplementation increased. There was no polynomial effect of OAM supplementation on blood parameters of the hens, except for glucose, alkaline phosphatase, calcium and phosphorus (P > 0.05). The inclusion of different percentages of OAM in the diet of laying hens did not affect villus height, but villus width (linear), intestinal crypt depth and tunica mucosal width (cubic) increased. The inclusion of 1.5 kg/t of feed OAM in the diet resulted in better FCR than in the control and other treatment groups. The results of the present study indicated that in response to increasing levels of OAM supplementation in the diet of laying hens, shell strength and yolk color increased. The inclusion of OAM in the diets exhibited benefits to intestine histology. In conclusion, it can be said that 1.5 kg/t OAM might be used in diets of laying hens.
Einfluss der Zulage einer Mischung von Organischen Säuren zum futter in unterschiedlicher Höhe auf leistung, eiqualitätsmerkmale, Blutserum-Kennwerte und Dünndarmmorphologie von Legehennen
Keywords: Laying hens; feeding; organic acids; egg quality; performance; blood serum; intestinal histology